A colour atlas of otorhinolaryngology - Benjamin, Bruce; Bingham, Brian; Hawke, Michael (Dunitz, 1997)
Winner, Royal Society of Medicine 1995 Atlas Award
Keywords: atlasy; Otolaryngology; otorinolaryngologie